Elucidating Axonal Injuries Through Molecular Modelling of Myelin Sheaths and Nodes of Ranvier - Saeedimasine, Marzieh; Montanino, Annaclaudia; Kleiven, Svein; Villa, Alessandra (Frontiers in Molecular Biosciences, 2021)
Around half of the traumatic brain injuries are thought to be axonal damage. Disruption of the cellular membranes, or alternatively cytoskeletal damage has been suggested as possible injury trigger. Here, we have used molecular models to have a better insight on the structural and mechanical properties of axon sub-cellular components. We modelled myelin sheath and node of Ranvier as lipid bilayers at a coarse grained level. We built ex-novo a model for the myelin. Lipid composition and lipid saturation were based on the available experimental data. The model contains 17 different types of lipids, distributed asymmetrically between two leaflets. Molecular dynamics simulations were performed to characterize the myelin and node-of-Ranvier bilayers at equilibrium and under deformation and compared to previous axolemma simulations. We found that the myelin bilayer has a slightly higher area compressibility modulus and higher rupture strain than node of Ranvier. Compared to the axolemma, mechanoporation occurs at 50 % higher strain in the myelin and at 23 % lower strain in the node of Ranvier. Combining the results with finite element simulations of the axon, we hypothesizes that myelin does not rupture at the thresholds proposed in the literature for axonal injury while rupture may occur at the node of Ranvier. The findings contribute to increases our knowledge of axonal sub-cellular components and help to understand better the mechanism behind axonal brain injury.